2018
DOI: 10.1136/heartjnl-2018-313452
|View full text |Cite
|
Sign up to set email alerts
|

Influence of myocardial scar on the response to frequent premature ventricular complex ablation

Abstract: ObjectiveThis study aims to evaluate the influence of myocardial scar after premature ventricular complexes (PVC) ablation in patients with left ventricular (LV) dysfunction.Methods70 consecutive patients (58±11 years, 58 (83%) men, 23% (18–32) mean PVC burden) with LV dysfunction and frequent PVCs submitted for ablation were included. A late gadolinium enhancement cardiac magnetic resonance (LGE-CMR) was performed prior to the ablation and a quantitative and qualitative analysis of the scar was done.ResultsLe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(11 citation statements)
references
References 20 publications
0
11
0
Order By: Relevance
“…Cardiac imaging is key to identify LV dysfunction and suspect the diagnosis of PVC-CM in patients with high PVC burden (≥10%) (Table 5). Cardiac MR with lategadolinium enhancement has the advantage of identifying scar and quantify scar burden, which in turn potentially predicts response to PVC suppression (84). Few clinical and animal studies have also demonstrated diastolic dysfunction after 12-weeks of chronic ventricular bigeminy (50,85).…”
Section: Clinical Presentation Diagnosis and Imaging Featuresmentioning
confidence: 99%
“…Cardiac imaging is key to identify LV dysfunction and suspect the diagnosis of PVC-CM in patients with high PVC burden (≥10%) (Table 5). Cardiac MR with lategadolinium enhancement has the advantage of identifying scar and quantify scar burden, which in turn potentially predicts response to PVC suppression (84). Few clinical and animal studies have also demonstrated diastolic dysfunction after 12-weeks of chronic ventricular bigeminy (50,85).…”
Section: Clinical Presentation Diagnosis and Imaging Featuresmentioning
confidence: 99%
“… 4 Importantly, a scar mass <9 g (cardiac magnetic resonance) predicts LV recovery. 51 Besides improving LV function, PVC ablation may also improve survival or long-term outcomes as suggested by the Congestive heart failure: Survival trial of antiarrhythmic therapy (CHF-STAT) study and the Grupo de Estudio de la Sobrevida en la Insuficiencia Cardiaca en Argentina (GESICA) trial. 40 , 52 Future clinical studies are clearly needed to better understand the clinical impact of PVC-CM and its treatment.…”
Section: Introductionmentioning
confidence: 99%
“…The half-width full-maximal method was used to define scar; thresholds for scar core and total scar were 50% and >35% of the maximal signal intensity, respectively. Both volumes were quantified and expressed in cm 3 .…”
Section: Methodsmentioning
confidence: 99%
“…Demonstration of delayed enhancement by cardiac magnetic resonance imaging (DE-CMR) is the gold standard for identification of myocardial scar. 1 Identifying cardiac scar in patients with frequent premature ventricular contractions (PVCs) helps with risk stratification 2 , 3 and procedural planning. However, the prevalence and the predictors of cardiac scar among this population are unknown.…”
Section: Introductionmentioning
confidence: 99%